2021
DOI: 10.4103/jcar.jcar_3_21
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinicopathological profile of gall bladder cancer patients: Study from a tertiary care center of the sub-himalayan region in indo-gangetic belt

Abstract: INTRODUCTION: Gall bladder cancer (GBC) accounts for 80%-95% of biliary tract malignancies in the world. There is however striking variability in the global incidence of gallbladder cancer, reaching epidemic levels for some regions and ethnicities. The aim of this study was to evaluate the demographic and clinicopathological profile of the gallbladder cancer patients. MATERIALS AND METHODS: All patients of carcinoma gall bladder presenting to department of surgery in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…In our study GBC was most commonly found in the 41-60 years age group and approximately 70% of cases were above 50 years of age. The mean age was 54 years which was similar to study done in Uttarakhand by Gupta A et al 10 In our evaluation of stages of GBC; 33% of the patients (8 out of 24 patients) were in stage II, while 29% (7 out of 24 patients) were having stage IIIB. Only 25% (6 out of 24 patients) presented in stage I disease, suggesting GBC to be a disease of advanced presentation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In our study GBC was most commonly found in the 41-60 years age group and approximately 70% of cases were above 50 years of age. The mean age was 54 years which was similar to study done in Uttarakhand by Gupta A et al 10 In our evaluation of stages of GBC; 33% of the patients (8 out of 24 patients) were in stage II, while 29% (7 out of 24 patients) were having stage IIIB. Only 25% (6 out of 24 patients) presented in stage I disease, suggesting GBC to be a disease of advanced presentation.…”
Section: Discussionsupporting
confidence: 87%
“…Whereas, Gupta A et al and Rawla P et al in their studies reported that majority of patients belonged to advanced stage (stage III & IV) of cancer. 10,15 This difference may be due to variation in geographical distribution or difference in sample size of the studies. Over 80% of GBC are adenocarcinomas arising from fundus (60%), followed by body and neck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For IGBC, radical cholecystectomy needs to be performed within 6–8 weeks of the first surgery, 27 but the majority of patients at TMC presented later than that, often with metastatic disease. The lower incidence of IGBC previously reported 11 suggests that patients are presenting at more advanced stages. Nevertheless, the insidious onset with non‐specific symptoms makes an early diagnosis difficult and most patients still present with advanced disease.…”
Section: Discussionmentioning
confidence: 78%
“…The average age of GB cancer patients was 55 ± 16 yr, much older than the overall average age of 39.5 yr. Univariate analysis performed for age comparison among GB cancer and other cases of cholelithiasis found the p-value (< 0.001) to be significant, signifying age to be a risk factor for GB carcinoma. Gupta et al [11] noted that the average age in gall bladder cancer was 51 ± 11 yr while Rathore et al [12] found the average age to be 52.4 yr. The mean age of presentation of GB carcinoma in India is younger than the average age in the USA and western European countries [13].…”
Section: Discussionmentioning
confidence: 99%